Genetic analyses of the mannitol permease of Escherichia coli: isolation and characterization of a transport-deficient mutant which retains phosphorylation activity. - Manayan, R (1988)
Three positive selection procedures were developed for the isolation of plasmid-encoded mutants which were defective in the mannitol enzyme II (IIMtl) of the phosphotransferase system (mtlA mutants). The mutants were characterized with respect to the following properties: (i) fermentation, (ii) transport, (iii) phosphoenolpyruvate(PEP)-dependent phosphorylation, and (iv) mannitol-1-phosphate-dependent transphosphorylation of mannitol. Cell lysis in response to indole acrylic acid, which causes the lethal overexpression of the plasmid-encoded mtlA gene, was also scored. No correlation was noted between residual IIMtl activity in the mutants and sensitivity to the toxic effect of indole acrylic acid. Plasmid-encoded mutants were isolated with (i) total or partial loss of all activities assayed, (ii) nearly normal rates of transphosphorylation but reduced rates of PEP-dependent phosphorylation, (iii) nearly normal rates of PEP-dependent phosphorylation but reduced rates of transphosphorylation, and (iv) total loss of transport activity but substantial retention of both phosphorylation activities in vitro. A mutant of this fourth class was extensively characterized. The mutant IIMtl was shown to be more thermolabile than the wild-type enzyme, it exhibited altered kinetic behavior, and it was shown to arise by a single nucleotide substitution (G-895----A) in the mtlA gene, causing a single amino acyl substitution (Gly-253----Glu) in the permease. The results show that a single amino acyl substitution can abolish transport function without abolishing phosphorylation activity. This work serves to identify a site which is crucial to the transport function of the enzyme.